25th Anniversary Article: Double Emulsion Templated Solid Microcapsules: Mechanics And Controlled Release. (24th February 2014) - Datta, Sujit S.; Abbaspourrad, Alireza; Amstad, Esther; Fan, Jing; Kim, Shin‐Hyun; Romanowsky, Mark; Shum, Ho Cheung; Sun, Bingjie; Utada, Andrew S.; Windbergs, Maike; Zhou, Shaobing; Weitz, David A.
<x xml:space="preserve">Abstract</x> How droplet microfluidics can be used to fabricate solid‐shelled microcapsules having precisely controlled release behavior is described. Glass capillary devices enable the production of monodisperse double emulsion drops, which can then be used as templates for microcapsule formation. The exquisite control afforded by microfluidics can be used to tune the compositions and geometrical characteristics of the microcapsules with exceptional precision. The use of this approach to fabricate microcapsules that only release their contents when exposed to a specific stimulus – such as a change in temperature, exposure to light, a change in the chemical environment, or an external stress – only after a prescribed time delay, and at a prescribed rate is reviewed.